Bad dreams - Fine, Anne. (London : Corgi Yearling Books, 2000)
Despite her preference for books over friends, Melanie gradually becomes involved with a new classmate and determined to find the reason for her strange behavior.
School Library Journal
Wilson's Children
Wilson's Junior High School
6.9
5-8
5-8
Keywords: Books and reading -- Fiction; Friendship -- Fiction; Magic -- Fiction; Schools -- Fiction; Books and reading -- Fiction; Friendship -- Fiction; Magic -- Fiction; School stories